Peranan Karakteristik Individu dan Stress Kerja terhadap Kepuasan Kerja Anggota Kepolisian Resor Malang - Noermijati Noermijati; Widya Nuryana (Jurnal Aplikasi Manajemen, 2012)
This research is observing individual characteristic, job stress, and job satisfaction in Malang police Department's members. The objective of this research is to analyze the effect of individual characteristic toward job stress and job satisfaction, the effect of job stress toward job satisfaction and the effect of individual characteristic toward job satisfaction through job stress. The research population is the member of operational division of police department, which are : samapta, lantas, intelkam, reskrim dan reskoba. Research sample consist of 80 police department members. Data collection done using questionnaire. Path analysis method is used to test research hypothesis. Research result shows that individual characteristic significantly affect job stress in negative way. The stronger individual character, the better he deals with pressure, so he would not to be stressed easily. Individual characteristic will encourage individuals to have high job satisfaction. Job stress significantly affect job satisfaction in negative way. Stressed individual tend to have lower job satisfaction.